Kepastian Status Halal-Haram Pada Produk Makanan Tanpa Label Halal Ditinjau Dengan Kaidah Al-Yakinu La Yuzalu Bisy-Syakk - Juliana Hikmatul Izmy (4, 2026)
Muslim communities often experience fear and doubt due to the increasing number of food products without halal labels. Through an analysis of the Islamic legal principle